Unbelievable happiness and final sorrow : the Hemingway-Pfeiffer marriage - Hawkins, Ruth A., 1947- (University of Arkansas Press, 2012)
Ruth A. Hawkins has been an administrator at Arkansas State University in Jonesboro for more than thirty years and established its Arkansas Heritage Sites program, which includes the Hemingway-Pfeiffer Museum in Piggott. She has been recognized at the state, regional, and national level for her work in historic preservation and heritage tourism.